Cysteine residues mediate high‐affinity binding of thioredoxin to ASK1. (18th September 2016) - Kylarova, Salome; Kosek, Dalibor; Petrvalska, Olivia; Psenakova, Katarina; Man, Petr; Vecer, Jaroslav; Herman, Petr; Obsilova, Veronika; Obsil, Tomas
Abstract : Apoptosis signal‐regulating kinase 1 (ASK1, MAP3K5) activates p38 mitogen‐activated protein kinase and the c‐Jun N‐terminal kinase in response to proinflammatory and stress signals. In nonstress conditions, ASK1 is inhibited by association with thioredoxin (TRX) which binds to the TRX‐binding domain (ASK1‐TBD) at the N terminus of ASK1. TRX dissociates in response to oxidative stress allowing the ASK1 activation. However, the molecular basis for the ASK1:TRX1 complex dissociation is still not fully understood. Here, the role of cysteine residues on the interaction between TRX1 and ASK1‐TBD in both reducing and oxidizing conditions was investigated. We show that from the two catalytic cysteines of TRX1 the residue C32 is responsible for the high‐affinity binding of TRX1 to ASK1‐TBD in reducing conditions. The disulfide bond formation between C32 and C35 within the active site of TRX1 is the main factor responsible for the TRX1 dissociation upon its oxidation as the formation of the second disulfide bond between noncatalytic cysteines C62 and C69 did not have any additional effect. ASK1‐TBD contains seven conserved cysteine residues which differ in solvent accessibility with the residue C250 being the only cysteine which is both solvent exposed and essential for TRX1 binding in reducing conditions. Furthermore, our data show that the catalytic site of TRX1 interacts with ASK1‐TBD region containing cysteine C200 and that the oxidative stress induces intramolecular disulfide bond formation within ASK1‐TBD and affects its structure in regions directly involved and/or important for TRX1 binding. Abstract : Apoptosis signal‐regulating kinase 1 (ASK1, MAP3K5) activates p38 and c‐Jun kinases in response to proinflammatory and stress signals. ASK1 is inhibited by association with thioredoxin (TRX) which dissociates in response to oxidative stress, thus allowing the ASK1 activation. Here, we investigated the role of cysteine residues on the interaction between TRX1 and ASK1 in both reducing and oxidizing conditions.